Interface Engineering for Extremely Large Grains in Explosively Crystallized TiO2 Films Grown by Low-Temperature Atomic Layer Deposition - Cho, Cheol Jin; Kang, Jun-Yun; Lee, Woo Chul; Baek, Seung-Hyub; Kim, Jin-Sang; Hwang, Cheol Seong; Kim, Seong Keun (AMER CHEMICAL SOC, 2017)
Functionality in thin films is closely linked with both the microstructure of the film as well as the innate nature of the thin film material. The engineering of microstructure, especially the grain size and its distribution in oxide thin films, is critical to designing functionalities targeting specific applications. However, the scope for manipulation of the microstructure of an oxide thin film is generally quite limited because of the lack of mobility of atoms at processing temperatures that are usually employed for the growth of these films. This work reports the observation of very large grains (similar to 100 times larger than the film thickness) in TiO2 films grown by atomic layer deposition at low temperature (<250 degrees C). Large grain sizes were observed in the as-grown films even in the absence of postdeposition annealing, wherein substrates with high surface energies were used. It is concluded that the surface energy engineering of substrate offers an efficient method to control the grain size of TiO2 films in low thermal budget processes. The results will provide facile routes to design novel properties of thin films via controlling the grain size even in low temperature processes.
Keywords: THIN-FILMS; TITANIUM-DIOXIDE; SURFACE-ENERGY; NANOPARTICLES; TRANSITION; STABILITY; EPITAXY; SILICON; ANATASE; METALS